Racial diversity in South African corporate boards and shareholder value creation: A decadal study - Zvinowanda, Douglas; Mafini, Chengedzai; Beneke, John D (International Journal of Management and Sustainability, 2025)
This study investigates the influence of board racial diversity (BRD) on shareholder value creation (SVC) of 95 non-financial companies listed on the Johannesburg Stock Exchange (JSE) from 2013 to 2022. The study employed a quantitative quasi-experimental method. The fixed effects model (FEM) was used to test the hypotheses. The results of linear FEM revealed that standard market value added was negatively influenced by the proportion of black directors (PBD), the Blau index for board racial diversity(BI_BRD) and dummies for skewed board (SB), tilted (TB) and balanced board (BB), while positively impacted by dummies for one Black director (BD1), two Black directors (BD2) and three or more Black directors (BD3). The market-to-book ratio was negatively influenced by BI_BRD and SB while positively impacted by PBD, BD1, BD2, BD3, TB and BB. Similarly, Tobin’s Q was negatively affected by PBD, BI_BRD, BD3, SB, TB and BB while positively impacted by BD1 and BD2. The curvilinear quadratic results of FEM revealed that PBD and BI_BRD positively impacted all SVC measures while PBD2 and BI_BRD2 negatively impacted all SVC measures, highlighting an inverted U-shaped effect. Thus, the results revealed that BRD has a double-edged sword effect in creating and maximising shareholder value.